MOTIVASI DAN BEBAN KERJA PERAWAT BERKAITAN DENGAN PENERAPAN KOMUNIKASI TERAPEUTIK PADA PASIEN GANGGUAN JIWA - Dalope, Felani; Ake, Julianus; Wetik, Syenshie (Lasalle Health Journal, 2024)
Introduction: The application of therapeutic communication in nursing services is crucial as it significantly impacts the patient's recovery process. Ineffective communication can lead to inappropriate treatment or recovery, and treatment planning may not be suitable for patients with mental health issues. Several factors can contribute to nurses having ineffective communication, including high workloads and decreased work motivation. Objective: This study investigates the correlation between nurse workload and their motivation with the implementation of therapeutic communication for patients with mental disorders. Method: A quantitative study using a cross-sectional design with a population of 150 nurses at RSJ Prof. Dr. V. L. Ratumbuysang in Manado and a sample size of n=60. Results were analyzed using chi-square and Fisher's exact test. Results: There is a significant relationship between nurse motivation and the implementation of therapeutic communication for patients with mental disorders, with a p-value of 0.032 < 0.05. However, there is no significant relationship between nurse workload and the implementation of therapeutic communication for patients with mental disorders, with a p-value of 1.000 > 0.05. Conclusion: The variable of motivation affects the implementation of therapeutic communication for patients with mental disorders, whereas the variable of workload does not.